2011
DOI: 10.1038/srep00020
|View full text |Cite
|
Sign up to set email alerts
|

An SNP selection strategy identified IL-22 associating with susceptibility to tuberculosis in Chinese

Abstract: Recent studies showed that IL-22 plays a protective role in the host defense. However, the contribution of polymorphisms of the IL-22 gene to human TB susceptibility remains untested. We have designed a computational approach to select functional SNPs in the IL-22 gene and genotyped them in a two-stage case-control study in Chinese (479 cases and 358 controls). We found that rs2227473, an SNP in the promoter region of IL-22, is associated with TB susceptibility at both stages of our study. The SNP shows associ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
51
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(55 citation statements)
references
References 35 publications
4
51
0
Order By: Relevance
“…In line with our results, it was previously demonstrated that the IL-22 response also dominated over the IL-17 response in patients with pulmonary tuberculosis (46). Moreover, IL-22 was shown to be important in the defense against multiple pulmonary pathogens including Mycobacterium tuberculosis (14,46,47), Klebsiella pneumoniae (48), and influenza A virus (16). Because the host defense against these pulmonary pathogens seems to strongly rely on IL-22, we hypothesize that IL-22 might play a pivotal role in the human anti-Aspergillus pulmonary host defense.…”
Section: Discussionsupporting
confidence: 80%
“…In line with our results, it was previously demonstrated that the IL-22 response also dominated over the IL-17 response in patients with pulmonary tuberculosis (46). Moreover, IL-22 was shown to be important in the defense against multiple pulmonary pathogens including Mycobacterium tuberculosis (14,46,47), Klebsiella pneumoniae (48), and influenza A virus (16). Because the host defense against these pulmonary pathogens seems to strongly rely on IL-22, we hypothesize that IL-22 might play a pivotal role in the human anti-Aspergillus pulmonary host defense.…”
Section: Discussionsupporting
confidence: 80%
“…This will provide answers pertaining to this subset and transcriptional signatures in patients from an endemic area or with different disease states. Our transcriptional analysis revealed that CCR6 + CXCR3 + CCR4 − cells preferentially express CCR2 and IL12 receptor and upon activation produce large amounts of CCL4 and IL-22, all of which have been implicated in higher susceptibility to TB infection (22, 23, 30, 31). Understanding the characteristics of CCR6 + CXCR3 + CCR4 − cells that provide them with the ability to contain TB infection should in turn provide better correlates of efficacy for TB vaccine development, which are currently lacking, and might also suggest specific pathways that can be exploited for development of antimycobacterial drugs.…”
Section: Discussionmentioning
confidence: 92%
“…CSF-1 has also been shown to play a role in the adaptive immune response against TB (29). Interestingly, mutations in the CCL4 (30) and IL22 (31) loci have been associated with increased susceptibility to TB. Overall, these data reinforce that CCR6 + CXCR3 + CCR4 − cells are capable of producing a broad spectrum of cytokines that contribute to their ability to contain LTBI.…”
Section: Resultsmentioning
confidence: 99%
“…Isolated DNA was stored at −80°C before usage. SNPs were selected according to methods described previously [16], with focusing on their potential regulatory roles, such as transcription binding sites in the promoter region, microRNA target sites in the 3′ untranslated region (UTR), protein phosphorylation sites in the extrons and other putative regulation sites.…”
Section: Methodsmentioning
confidence: 99%